Big Five model and trait emotional intelligence in camouflaging behaviours in autism. (1st January 2020) - Robinson, Erin; Hull, Laura; Petrides, K.V.
Abstract: This study investigated the association of the five-factor model and trait emotional intelligence (trait EI) with camouflaging behaviours (masking and compensating for autistic characteristics) in a large sample of 278 autistic and 230 typically developing (TD) participants. Participants completed questionnaires assessing autistic traits, big five personality, trait EI, and social camouflaging of autistic traits. Camouflaging was negatively related to extraversion, agreeableness, and conscientiousness, while it was positively related to neuroticism. Trait EI was also negatively linked to camouflaging. The differences between autistic and TD participants regarding camouflaging are discussed. Additionally, associations between the dimensions of extraversion, agreeableness, conscientiousness, and neuroticism with autistic traits were found, supporting previous research showing that individuals with higher autistic traits are predisposed to specific personality traits. Trait EI had a negative relationship with autistic traits, suggesting a specific emotional difficulty for individuals with high autistic traits.